Water balance - lake water level from Erssjön - Skogaryd Research Catchment (University of Gothenburg, 2025)
Accurate measurements of the lake water level for the lakes in SITES Water.
Skogaryd Research Catchment (2025). Water balance - lake water level from Erssjön, 2017-02-07–2024-07-30 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/JT_9xgWoqtqk8zNhqcty8XrX
Keywords: Skogaryd Research Catchment; Lake levels; Lake/Pond; Time instant; Time instant; Lake level; Lake level; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap